Peningkatan Kreatifitas dan Hasil Belajar Matematika Materi Peluang melalui Pemanfaatan Alat Peraga "Bu Kardu" bagi Siswa Kelas VII RPL A SMK N Tembarak pada Semester Gasal Tahun Pelajaran 2014/2015 - Rokhaeni, Asih (widiyanto, 2016)
The purpose of this research is to improve creativity and the result of material opportunities on maths' studies of the students on class XII RPL A in old semester 1014/2015 through utilization of props Bu Kardu. The subject of research is the students of Tembarak Vocational High School class XII RPL A school year 2014/2015, consisting of 35 students, 20 students are male and 15 female students. This research uses techniques of observation and documentation that the results will be comparing since pre-cycle activity, 1st and 2nd cycle. The result of this research show the process of learning mathematics opportunities material that done by utilizing props Bu Kardu can increase creativity and learning results.